2020
DOI: 10.1016/j.pld.2020.01.003
|View full text |Cite
|
Sign up to set email alerts
|

Cold stratification, temperature, light, GA3, and KNO3 effects on seed germination of Primula beesiana from Yunnan, China

Abstract: Primula beesiana Forr. is an attractive wildflower endemically distributed in the wet habitats of subalpine/alpine regions of southwestern China. This study is an attempt to understand how this plant adapts to wet habitats and high altitudes. Specifically, we examined the effects of cold stratification, light, GA 3 , KNO 3 , and temperature on P. beesiana seed germination. KNO 3 and GA 3 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
29
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 40 publications
(37 citation statements)
references
References 24 publications
7
29
0
1
Order By: Relevance
“…Nitrogenous compounds, such as nitrate, NO and cyanide, have a positive effect on the release of dormancy [39][40][41]. Wang reported that the application of nitrate in potato promoted the expression of a gene involved in ABA catabolism (StCYP707A1) [42].…”
Section: Plant Growth Regulators Regulation On Plant Seed Germinationmentioning
confidence: 99%
“…Nitrogenous compounds, such as nitrate, NO and cyanide, have a positive effect on the release of dormancy [39][40][41]. Wang reported that the application of nitrate in potato promoted the expression of a gene involved in ABA catabolism (StCYP707A1) [42].…”
Section: Plant Growth Regulators Regulation On Plant Seed Germinationmentioning
confidence: 99%
“…External GA 3 can act as a stimulator for internal GA 3 synthesis 17 . Gibberellins play a role in breaking the dormancy, accelerating the germination and flowering time 49 and increasing the vegetative growth by affecting the synthesis and activity of hydrolyzing enzymes in storage resources 50 . In addition, gibberellins improve the photosynthetic efficiency by enhancing photosynthetic enzymes and leaf area index and increasing the nutrient uptake 51 .…”
Section: Discussionmentioning
confidence: 99%
“…The plant growth regulators are divided into ve classes, one of them being Gibberellin (GA), which is a diterpenoid compound, and the most active arti cially synthesized hormone [28,29]. A previous studies showed that the germination rate of Primula beesiana seeds under 15/5℃ treatment was less than 10%, but exogenous GA 3 signi cantly increased seed germination [30]. In this study, exogenous GA 3 signi cantly promoted seed germination, enhanced germination rate, promoted the growth and elongation of the hypocotyl in Phellodendron chinense Schneid ( Fig.…”
Section: Discussionmentioning
confidence: 99%